Methemoglobinemia in a child with congenital epidermolysis bullosa - Ya. A. Lezhepekova; K. V. Pshenisnov; Y. S. Aleksandrovich (Вестник анестезиологии и реаниматологии, 2024)
Introduction .  Methemoglobinemia is a rather rare cause of hypoxemia and hypoxia, however, with a severe course of the disease and an increase in the concentration of methemoglobin in the blood of more than 20 %, this can cause the development of multi-organ dysfunction and death.The objective was to descript the case of methemoglobinemia in a child with congenital epidermolysis bullosa with the use of a combined drug containing benzocaine.Materials and methods.  Newborn premature baby boy, from the first pregnancy, gestation period 36 weeks, suffering from congenital epidermolysis. Birth weight 2850 g, height 47 cm. Apgar score in the first minute – seven, on the fifth – eight points. As a local treatment, an aerosol for external use «Olazol» was prescribed. At the age of 56 hours from the moment of birth, a sharp deterioration in the child’s condition  was noted in the form of a decrease in SpO2 to 72–76 %, pronounced tachycardia, an increase in methemoglobin concentration in the blood (53.7 %).Results.  A distinctive feature of this case was the presence of severe methemoglobinemia, which led to severe metabolic acidosis, venous hypoxemia and tissue hypoxia. Timely diagnosis and adequate therapy in the early stages of the pathological process contributed to the  complete stabilization of the child’s condition and the normalization of the blood gas composition fifteen hours after the start of therapy.Conclusion.  The use of drugs containing benzocaine in the early neonatal period is a risk factor for the development of methemoglobinemia, which requires a dynamic assessment of the level of methemoglobin in the blood in order to prevent tissue hypoxia.